EFFECT OF HELIUM-NEON LASER ON THE LYMPHOCYTE CELLS AND THEIR DNA (Iraqi Journal of Medical Sciences, 2017)
Background: Laser light is widely used for a wide range of medical applications. He-Ne laser application in medicine as in any type of laser is based on the interaction of laser light with the biological system.Objective: To show the effect of helium-neon (He-Ne) laser (632.8 nm) irradiation on human lymphocyte blood cells and their DNA.Methods: This study involved 72 blood samples, taken from apparently healthy volunteers. The samples were divided into two groups; the 1st group consisted of 27 samples were processed only for lymphocyte blood cells separation, while the 2nd group, which consisted of 45 samples were employed to evaluate the influence of He-Ne laser irradiation on the extracted DNA from the lymphocyte blood cells.Results: At the used doses of He-Ne laser (18, 35, 52.5, and 69 J/m²), a significant difference was found (P < 0.05) in survival percentage of lymphocyte cells (99.8, 99.74, 99.68, and 99.59) in comparison with those cells untreated with He-Ne laser irradiation. Immediately after He-Ne laser irradiation alone, the following doses (18, 35, and 69 J/m²) were applied on the extracted DNA, the DNA demonstrated a significant damaging where the fraction of DNA survival percentage was (88.6, 87.7, 86.1) respectively, with significant difference (P < 0.05) between the DNA survival before and after He-Ne laser irradiation.Conclusion: The percentage of lymphocytes survival is decreasing with increasing dose of He-Ne laser and longer exposure time where time exposure (2.5, 5, 7.5, and 10 s). He-Ne laser irradiation causes a significant degree of DNA damaging independent on the irradiation doses.Keywords: Lymphocyte cells, He-Ne laser irradiation, DNA. Citation: Abdullah SS, Taha JH, Ahmed MH. Effect of Helium-Neon Laser on the Lymphocyte Cells and their DNA. Iraqi JMS. 2017; Vol. 15(3): 275-282. doi: 10.22578/IJMS.15.3.9
Keywords: Lymphocyte cells; HeNe laser irradiation; DNA